1995
DOI: 10.7124/bc.000400
|View full text |Cite
|
Sign up to set email alerts
|

Genome variability in plant somatic cells. 2. Natural variability

Abstract: Геномная изменчивость соматических клеток растений. 2. Изменчивость в природе Сделан обзор литературных данных о геномной изменчивости соматических клеток интактных растении в норме и после различных воздействий. Проанализированы явления встречаемо сти, причины появления и биологическое значение химерных имиксоплоидных форм, особенности геномной изменчивости гибридов, гаплоидов и полиплоидов, изменчивость при ранении, привив ках и других стрессовых воздействиях. Особое внимание уделено анализу возможных причин… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Such karyological heterogeneity is consistent with observations of gametoclonal variants of triticale, wheat, rice. and other species (Kunakh, 1995).…”
Section: Resultsmentioning
confidence: 95%
“…Such karyological heterogeneity is consistent with observations of gametoclonal variants of triticale, wheat, rice. and other species (Kunakh, 1995).…”
Section: Resultsmentioning
confidence: 95%
“…The karyological analysis showed that mixoploidy was revealed in half of the studied samples. Some researchers believe that mixoploidy is associated with the adaptation of plants to unfavourable environmental conditions (Kunakh, 1995;Sedel'nikova et al, 2010;Kunakh, 2011). Thus, the appearance of polyploid cells can be considered as one of the regulatory mechanisms that allow maintaining a certain level of population resistance in extreme environmental conditions (Muratova and Sedel'nikova, 2004).…”
Section: Discussionmentioning
confidence: 99%